PERAN PEMANGKU KEPENTINGAN DAN FAKTOR-FAKTOR DALAM PENGELOLAAN PERBATASAN DI GUNUNG IJEN - Loetvy Wahyuningtiyas; Doddy Aditya Iskandar (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2023)
Regional governance on natural resources located in border region concerns on whether stakeholders’ decisions to interact one with another are influenced by their predetermined and assigned social and functional roles. This relationship between roles and interactions reveals whether stakeholders’ embedded capacity and formal authority (proxied by role of each stakeholder) would result in effective management and governance of border region. The paper aims to illuminate specific roles of stakeholders that influence and/or impede their interactions with other stakeholders. Drawing from the case of Mount Ijen bordering between Banyuwangi and Bondowoso in East Java, we analyze whether stakeholders’ roles and interactions are shaped by the specific characteristics of the area within the Mount Ijen region that lead to the emergence of particular governance mode. The research uses a qualitative approach with a case study method. The analysis techniques used are pattern matching and stakeholder. Two significant roles are identified: policy creators and facilitators, of which these two were influenced by physical aspects, institutional arrangements and legal binding concerns.